Performance Validation of PM Assisted SynRM and PMSM with Optimized Design for EV Application (2023)
This paper presents the comparison of Permanent Magnet-Assisted Synchronous Reluctance Motor (PMASynRM) and Permanent Magnet Synchronous Motor (PMSM) for the same design parameters and the evaluation of various performance parameters based on the Finite Element (FE) Method. FE Analysis is conducted after selecting the optimized design for PMASynRM and PMSM using an FE tool, with loading conditions to determine various performance parameters. This is achieved by maintaining the same motor dimensions and stator parameters while altering the rotor geometry for both motors. The final simulation results are discussed, and other performance parameters are recorded for comparison purposes. A PMASynRM is introduced, in which the problems of Synchronous Reluctance Motor (SynRM) can be eliminated with a permanent magnet in the rotor flux barrier. Due to higher flux barriers in PMASynRM, the reluctance torque is higher than in PMSM. If the magnet is placed very near to the air gap in PMSM, higher magnet torque is achieved, but due to the high reluctance torque in PMASynRM, the electromagnetic torque of PMASynRM is higher compared to PMSM. The research proves that the proposed design of PMASynRM is the best choice for Electric Vehicle (EV) applications. For PMASynRM, the shape of the flux barrier is not possible to change due to the design limitation of the FE software tool. Further analysis can be conducted by changing the shapes of the flux barriers to propose the most effective barriers. Basic theory and FE analysis of conventional PMSM and SynRM are reported in the literature. An optimal design is proposed through comparative analysis for EV applications to find out the best candidate for an EV motor.